The Role of Work-Life Balance in Mediating the Impact of Work From Home on Employee Performance: Abstract: - Martha Layuk Ada; Ernani Hadiyati; Umi Muawanah (International Journal of Economics Development Research (IJEDR), 2023)
This research was aimed to discover and analyze the impact of Working from Home on employee performance with Work-Life Balance as the mediating variable. It used a quantitative approach with primary data. The data collection technique was conducted through questionnaires distributed to 76 respondents via Google Forms. The data analysis technique was SmartPLS-SEM. The research findings reveaedl that Work from Home creates a positive and significant impact on Work-Life Balance; Work-Life Balance impacts positively and significantly on employee performance; Work from Home brings a positive impact but not significant on employee performance; and Work from Home creates a positive and significant impact on employee performance with Work-Life Balance as the mediating variable.